Beyond Multiculturalism: An Interpretative Phenomenological Inquiry into Evolving Paradigms for Intercultural Counseling Practice - Pinasthika Patricia Br Ginting pina; Wahyu Widyatmoko; Yasinta Sari Pratiwi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Globalization and increasing cultural mobility have transformed contemporary counseling practice, challenging models that assume cultural homogeneity between counselors and clients. While multicultural counseling frameworks have contributed to greater cultural awareness, they often conceptualize culture in static and categorical terms. This study aims to examine evolving paradigms of intercultural counseling by moving beyond descriptive multicultural models toward a relational and interpretive understanding of counseling practice. Using a qualitative interpretive design, this study conducted a critical literature review of scholarly works on multicultural and intercultural counseling published between 2015 and 2024. The selected literature was analyzed through a hermeneutic–thematic approach informed by phenomenological principles to explore how counselors engage with cultural difference in practice. The analysis identified four interrelated dimensions shaping intercultural counseling encounters: constructions of self and identity, culturally embedded interpretations of psychological distress, expectations toward the counselor–client relationship, and socio-economic conditions associated with migration experiences. These dimensions highlight the limitations of culturally neutral or universally applied counseling models and emphasize the importance of interaction, reflexivity, and contextual sensitivity.The study concludes that an intercultural counseling perspective provides a more comprehensive framework for understanding contemporary counseling practice in culturally diverse contexts. By conceptualizing culture as dynamic and relational, this approach offers theoretical and practical insights for developing counseling practices that are responsive to increasing cultural complexity in a globalized world